The Phonetic Level between Algerian Colloquial Arabic and Standard Arabic (Deletion and Substitution) - souiah, fatna; zeroki, aboubaker (El Omda in Linguistics and Discourse Analysis, 2024)
The phonetic study represents the first level of linguistic analysis, as linguistic research is concerned with studying linguistic sounds from multiple aspects, and with different considerations, as they are independent phonemic units isolated from the verbal context. General phonology is the science that is concerned with the phonological aspect; it is concerned with the statement of the exits of sounds, ways of pronunciation, as well as their qualities and how to produce them. Our study aims to study the phonemic level in the standard Arabic language as well as in the Algerian slang, according to the comparative approach to show similarities and differences. Between standard Arabic and Algerian slang, what is the difference between phonetic study in standard Arabic and Algerian slang?